1992
DOI: 10.1113/jphysiol.1992.sp019393
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the ventilatory response in man to step changes of end‐tidal carbon dioxide and of hypoxia during exercise.

Abstract: SUMMARY1. Four human subjects exercised in hypoxia (end-tidal partial pressure Of 02 (PET, 02) ca 55 Torr; heart rate ca 100-130 beats min-), and the contribution to the respiratory drive of the peripheral and central chemoreflex pathways have been separated on the basis of the latencies and the time courses of the responses to sudden changes of stimulus.2. The subjects were exposed to repeated end-tidal step changes in PCO2 of ca 3-3 5 Torr (at nearly constant PET, 02 ) and P02 (between ca 55 and 230 Torr) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…This finding indicates that the transfer function gain curve from P ETCO 2 toV E response resets to the higher operating point during exercise. This finding is partly consistent with the previous studies that reported that exercise augmented the response of the central respiratory chemoreflex (MacFarlane & Cunningham, 1992;Ogoh et al, 2009). Exercise decreased τ of the onsetV E exponential fitting curve (Ogoh et al, 2009) and the transport delay time to the central respiratory chemoreflex (MacFarlane & Cunningham, 1992;Ogoh et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding indicates that the transfer function gain curve from P ETCO 2 toV E response resets to the higher operating point during exercise. This finding is partly consistent with the previous studies that reported that exercise augmented the response of the central respiratory chemoreflex (MacFarlane & Cunningham, 1992;Ogoh et al, 2009). Exercise decreased τ of the onsetV E exponential fitting curve (Ogoh et al, 2009) and the transport delay time to the central respiratory chemoreflex (MacFarlane & Cunningham, 1992;Ogoh et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is partly consistent with the previous studies that reported that exercise augmented the response of the central respiratory chemoreflex (MacFarlane & Cunningham, 1992;Ogoh et al, 2009). Exercise decreased τ of the onsetV E exponential fitting curve (Ogoh et al, 2009) and the transport delay time to the central respiratory chemoreflex (MacFarlane & Cunningham, 1992;Ogoh et al, 2009). The shortened central respiratory chemoreflex time delay during exercise seems to be associated with the faster onset response, potentially caused by the exercise-induced fast transmission of CO 2 from the lungs to the arterial blood (Ward & Bellville, 1983).…”
Section: Discussionsupporting
confidence: 91%
“…Third, we measured CBF after 8 min of hypoxia. This was believed to be sufficient to reach steady‐state levels of P aO 2 (MacFarlane & Cunningham, ). Also, when breathing was restrained in hypoxia, a higher level of attention, concentration and cognitive processing was needed to perform the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Both ICA and VA blood flow were assessed during ventilatory steady‐state conditions (MacFarlane & Cunningham, 1992; Willie et al 2012). Blood flow was measured a minimum of three times during a 2 min period within 10–15 min of exposure to hypoxia.…”
Section: Methodsmentioning
confidence: 99%